Use of electronic technologies in the University of the Philippines Diliman Libraries and its effects on users' information needs - Laxamana, Evelyn O. 1960- (2002)
This study was conducted to determine the following: (1) users needs and expectations in the use of electronic resources, (2) accessibility and availability of these resources to users, (3) obstacles faced in using these resources, and (4) users' degree of satisfaction in their use of the UP Diliman Library System Resources. Three hundred ninety five (395) library users were the respondents identified through purposive convenience random sampling. The data were gathered using a questionnaire patterned after Wenxiang Zhang (1998). Data gathered were organized, tabulated and analyzed using the Statistical Package for the Social Science (SPSS) software. The majority of the respondents are female (60 percent) undergraduate students (62 percent).